SISTEM INFORMASI PARIWISATA KABUPATEN KARANGANYAR MENGGUNAKAN GOOGLE MAPS - Fransisca Pranata; Wasino Wasino; Jap Tji Beng (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
Karanganyar has many attractions that are worth to visit, but the presence of the object - attractions in Karanganyar is still little known by tourists, both domestic and abroad due to their socialization still using conventional media such as booklets or brochures.A system of Karanganyar tourism information using Google Maps has been built and developed as an alternative media promotion and dissemination. With the construction of this system, it is expected to help expand information on the whereabouts of attractions owned by Karanganyar and can help facilitate travelers to determine their route, and information about the distance between attractions travel services and the roads to impassable. The methods used in data collection are direct observation, interviews and questionnaires.